2005
DOI: 10.1002/jms.870
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of synthetic nucleic acids by electrospray ionization quadrupole time‐of‐flight mass spectrometry

Abstract: The potential of electrospray ionization quadrupole-quadrupole-time-of-flight mass spectrometry (ESI-QqTOF-MS) for the characterization of synthetic nucleic acids was evaluated. Oligonucleotides ranging in size from 12 up to 51 nucleotides were analyzed via direct infusion MS as well as via liquid chromatography (LC) online hyphenated to MS. These experiments proved the outstanding mass spectrometric performance of the TOF mass analyzer in regard of accuracy, reproducibility, resolution, and sensitivity. Durin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
45
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 45 publications
(45 citation statements)
references
References 67 publications
0
45
0
Order By: Relevance
“…The QqTOF, which can be regarded as a triple quadrupole (QqQ) instrument where the third quadrupole is replaced by an orthogonal TOF, was originally used for rapid de novo peptide sequencing (Shevchenko et al, 1997) but has found application in many areas of research including metabolite (Levsen et al, 2005), nucleic acid (Oberacher, Niederstatter, & Parson, 2005) and glycoprotein (Morris et al, 2007) analysis. However, for scan-types in which a single ion is monitored such as precursor ion and neutral loss scans (important experiments for structural characterization), the sensitivity of the QqTOF (5-30% duty cycle) is lower than QqQ instruments because more ions are lost in TOF compared with a third quadrupole.…”
Section: Introductionmentioning
confidence: 99%
“…The QqTOF, which can be regarded as a triple quadrupole (QqQ) instrument where the third quadrupole is replaced by an orthogonal TOF, was originally used for rapid de novo peptide sequencing (Shevchenko et al, 1997) but has found application in many areas of research including metabolite (Levsen et al, 2005), nucleic acid (Oberacher, Niederstatter, & Parson, 2005) and glycoprotein (Morris et al, 2007) analysis. However, for scan-types in which a single ion is monitored such as precursor ion and neutral loss scans (important experiments for structural characterization), the sensitivity of the QqTOF (5-30% duty cycle) is lower than QqQ instruments because more ions are lost in TOF compared with a third quadrupole.…”
Section: Introductionmentioning
confidence: 99%
“…ESI-MS was performed on a QSTAR XL mass spectrometer (Applied Biosystems) equipped with a modified TurboIonSpray source [6,13]. The exit of the capillary column was connected directly to the transfer line by means of a microtight union (Upchurch Scientific, Oak Harbor, WA).…”
Section: Methodsmentioning
confidence: 99%
“…The exit of the capillary column was connected directly to the transfer line by means of a microtight union (Upchurch Scientific, Oak Harbor, WA). Mass calibration and optimization of instrumental parameters were performed in the negative ion mode as previously described [6,13]. The spray voltage was typically in the range of 3.0 to 3.5 kV.…”
Section: Methodsmentioning
confidence: 99%
“…The sequences of the PCR primers were taken from [6]. All oligonucleotides were obtained from Sigma-Aldrich and quality-checked by ICEMS [10] before use in PCR.…”
Section: Chemicals and Oligonucleotidesmentioning
confidence: 99%
“…The gradient was started 5 min after the sample injection event. Eluting nucleic acids were detected online by negative electrospray ionization-mass spectrometry which was performed on a QSTAR XL mass spectrometer (AB) equipped with a modified TurboIonSpray source [10,12]. Mass calibration and optimization of instrumental parameters was performed as described elsewhere [10,12].…”
Section: Experimental Setup For Icems Str Analysismentioning
confidence: 99%